2019
DOI: 10.1190/geo2018-0257.1
|View full text |Cite
|
Sign up to set email alerts
|

Constrained 3D inversion of magnetic data with structural orientation and borehole lithology: A case study in the Macheng iron deposit, Hebei, China

Abstract: We have developed a case study on the use of constrained inversion of magnetic data for recovering ore bodies quantitatively in the Macheng iron deposit, China. The inversion is constrained by the structural orientation and the borehole lithology in the presence of high magnetic susceptibility and strong remanent magnetization. Either the self-demagnetization effect caused by high susceptibility or strong remanent magnetization would lead to an unknown total magnetization direction. Here, we chose inversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…However, it has faced two major challenges: the problem of multiple solutions and the problem of computation time. Scholars have addressed these two issues by imposing additional constraints to constrain the inversion process and by carrying out deep research and applying optimizing inversion algorithms and using multi-core parallel technology to improve computation speed [30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has faced two major challenges: the problem of multiple solutions and the problem of computation time. Scholars have addressed these two issues by imposing additional constraints to constrain the inversion process and by carrying out deep research and applying optimizing inversion algorithms and using multi-core parallel technology to improve computation speed [30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…inversion algorithms and using multi-core parallel technology to improve computation speed [30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Such a big error (3,945 nT) has a deep negative impact on the interpretation and even absolutely mistake. The error between Δ T pro and Δ T true should be considered carefully when the data indicate high magnetic amplitudes 30 . To understand the difference between Δ T pro and Δ T true , we converted the magnetic anomalies to reduction to the pole (RTP) values for m = 50 A/m (Fig.…”
Section: Comparison Of the Projection And Modulus Difference Anomaliementioning
confidence: 99%
“…Coleman and Li 29 studied the difference between the errors of the total-field anomaly and magnetic amplitude data and found that the errors in the three orthogonal components converted from the total-field anomaly had similar standard deviations. Based on the total magnetic anomaly is no longer approximately equal to projection anomaly in the highly magnetic environments, Sun et al 30 used the information from the borehole data and structural orientation as constraints and get an acceptable result. In our study, we define the error between projection anomaly and observed modulus difference anomaly firstly and carefully discuss the error caused by amplitude, inclination and declination individually and together between the projection anomaly results (data processing, inversion and interpretation) with those of the modulus difference anomaly for strong magnetic anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…As for the second problem, the 3-D inversion method in which the CPD is incorporated in a geocentric SCS, can be addressed by the development of the inversion methods and their corresponding approaches with integrating geophysical and geological information in the CCS (e.g., Lelièvre & Oldenburg, 2009a;Li & Oldenburg, 1996Pilkington, 1997;Sun et al, 2019). Du et al (2013Du et al ( , 2014 applied a 3-D inversion approach in SCS to the magnetic data over Australia.…”
mentioning
confidence: 99%